Animal extrapolation in preclinical studies: An analysis of the tragic case of TGN1412. (February 2017) - Lemoine, Maël
Abstract: According to the received view, the transportation view, animal extrapolation consists in inductive prediction of the outcome of a mechanism in a target, based on an analogical mechanism in a model. Through an analysis of the failure of preclinical studies of TGN1412, an innovative drug, to predict the tragic consequences of its first-in-man trial in 2006, the received view is challenged by a proposed view of animal extrapolation, the chimera view . According to this view, animal extrapolation is based on a hypothesis about how human organisms work, supported by the amalgamation of results drawn from various experimental organisms, and only predicting the 'predictive grid', that is, a global framework of the effects to be expected. Highlights: Animal extrapolation does not always consist in an inductive, analogical argument based on the observation of mechanisms. It often relies on the hypothesis of a mechanism with piecemeal support of various animal models, i.e., an amalgamation of evidence. It is reliable at predicting kinds of effects to be expected, but not at predicting their magnitude.